Sistem Informasi dan Pers Islam (Pers Islam dalam Menyikapi Perubahan) - Usman Usman (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2012)
Islamic press in the growth and development can be seen in two forms, namely the press that sow Islam as Islam rubric, and the press that highlight Islam as breath, spirit, and commitment. Islamic conference that is shows the featuring Islam as rubric, usually intended as a means of propaganda. Islamic press is usually issued by Islamic institutions, such as community organizations, foundations, and institutions of Islamic education. While the Islamic press present Islam as breath, spirit, and commitment are managed by people who have a concern and commitment to the cause of Islam. Islamic press must be able to act as guardians of Islamic culture that is reliable, and able to become creators of culture in the professional intelligentsia